A face pobre da AIDS - Franco, Roberto Kennedy Gomes (2010)
In our research, we analyzed the proliferation of human immunodeficiency virus - HIV from the perspective of historical and dialectical materialism. The centrality of the text is an engaging way to expose the contradictions of contemporary capitalism through the poor face of AIDS. The common thread of analysis proceeds methodically through the articulation of different sources (oral and written). Historically, the onset of AIDS in Brazil occurred during the 1980s, initially affecting the social classes in higher education. Today, in the third decade of the pandemic, the research data clearly denounce the virus spreads so increasing social class with lower education, or AIDS specifically affects the poor. In the context of commercialization of health, estimates indicate that hegemonic, over 90% of cases of the AIDS pandemic is concentrated in certain countries of peripheral economies in Africa and Latin America. In fact, Brazilian educational history, the data show that about 50% of the serologically positive for HIV are poor and with very low educational level. The disease in this way reproduces the class contradictions of the sociability of the Capital. Coupled to this process, we analyze also the advent of political engagement characterized as activism to combat AIDS, particularly the Social Movement called the National Network of People Living with HIV / AIDS (RNP + Brazil). Organized in the 1990s, the associations triggered by this new social movement concerns the historical process of political awareness and mobilization for better health conditions for lives in bodily experiences of illness. It should be noted, however, the limit of political action reformist struggle for civil and human rights and not to break with the anti-capitalist democratic state Bourgeois.